ANALISIS DAN EVALUASI PENGGUNAAN METODE AGILE SCRUM DALAM PERANCANGAN SISTEM INFORMASI FOTOGRAFI - Setiawan, Wahyu Danni; Supangat, Supangat (LPPM Universitas Bina Bangsa, 2024)
In the ever-evolving digital era, the photography subsector is experiencing rapid growth with the advent of advanced technology. Despite this, photographers face obstacles in effectively promoting their services, especially for freelancers. The Agile Scrum method has become a potential approach in the development of photography information systems. With a focus on collaborative work in short iterations (sprints), this method allows developers to adapt to changing market needs quickly. The use of the Agile Scrum method in the design of photography information systems offers great benefits, especially in terms of transparency, prioritization of features based on value, and rapid adaptation to changes. Nonetheless, constraints such as limited experience, inaccurate time estimation, and the challenge of maintaining focus remain relevant. However, Agile Scrum still made a positive contribution in producing an adaptive and quality system according to the customer's needs